DAMAGE DETECTION OF SPACE STRUCTURES USING CHARGED SYSTEM SEARCH ALGORITHM AND RESIDUAL FORCE METHOD - Saberi, M; Kaveh, A (Iranian journal of science and technology. Transactions of civil engineering, 2015)
Changes in dynamic properties of structures indicate occurrence of damages in the structures. In this paper, a new two stage algorithm for damage detection of large structure is introduced. A modified Residual Force Method is utilized to locate the damage regions in structures, especially barrel vaults, and then the enhanced Charged System Search (CSS) Algorithm is used to quantify the amount of damage. The proposed method requires modeling the structure in its undamaged state to obtain the dynamic properties such as frequencies and mode shapes of the structure in its damaged state. The validation of the method is investigated by some numerical study on space structures. It is shown that if dynamic properties are not affected by noise, the method can still identify damaged elements, but when measurements are corrupted by noise, the exact determination of damaged region is not possible. To overcome this problem, it is proposed to repeat measuring modal properties several times, and then with utilizing residual force vector and statistical analysis, the damaged region is predicted accurately. In this paper, a modified vector is utilized for enhancing efficiency of the modal Residual Force method and suppressing effect of noise, and then a threshold is defined to distinguish DOFs associated with damaged elements. Then, using the CSS algorithm, severities of damaged elements are assessed.